A multi-center randomized trial of two different intravenous fluids during labor*. (17th January 2016) - Dapuzzo-Argiriou, Lisa M.; Smulian, John C.; Rochon, Meredith L.; Galdi, Luisa; Kissling, Jessika M.; Schnatz, Peter F.; Gonzalez Rios, Angel; Airoldi, James; Carrillo, Mary Anne; Maines, Jaimie; Kunselman, Allen R.; Repke, John; et al.
Abstract: Objective : To determine if the intrapartum use of a 5% glucose-containing intravenous solution decreases the chance of a cesarean delivery for women presenting in active labor. Methods : This was a multi-center, prospective, single (patient) blind, randomized study design implemented at four obstetric residency programs in Pennsylvania. Singleton, term, consenting women presenting in active spontaneous labor with a cervical dilation of <6 cm were randomized to lactated Ringer's with or without 5% glucose (LR versus D5LR) as their maintenance intravenous fluid. The primary outcome was the cesarean birth rate. Secondary outcomes included labor characteristics, as well as maternal or neonatal complications. Results : There were 309 women analyzed. Demographic variables and admitting cervical dilation were similar among study groups. There was no significant difference in the cesarean delivery rate for the D5LR group (23/153 or 15.0%) versus the LR arm (18/156 or 11.5%), [RR (95% CI) of 1.32 (0.75, 2.35), p  = 0.34]. There were no differences in augmentation rates or intrapartum complications. Conclusions : The use of intravenous fluid containing 5% dextrose does not lower the chance of cesarean delivery for women admitted in active labor.